Phosphorus and Potassium Fertilizer Rate Verification for a Corn–Wheat–Soybean Rotation System in Tennessee. (1st July 2019) - Singh, Surendra; Savoy, Hubert J.; Yin, Xinhua; Schneider, Liesel; Jagadamma, Sindhu
Abstract : Core Ideas: Phosphorus and potassium fertilizer rates for row crop systems of Tennessee were verified. Four cropping years were required before significant yield responses were observed. Application of >59 kg P ha −1 was required to build high soil test P. All tested K fertilizer rates failed to build soil K levels to high range. Soil test‐based fertilizer recommendations are necessary for profitable farming without adversely affecting the environment. The University of Tennessee (UT) stopped recommending P and K fertilizers in 2008 for soils with high Mehlich‐1 P and K levels because they were unprofitable. However, commercial laboratories tend to recommend higher fertilizer rates than UT, despite equivalent soil test results. To address this discrepancy, field trials were conducted from 2009 to 2015 for a corn ( Zea mays L.)–wheat ( Triticum aestivum L.)–soybean [ Glycine max (L.) Merr.] rotation on low‐ to medium‐testing soils at UT's Research and Education Centers at Milan and Springfield. Our specific objectives were to (i) evaluate yield responses to P and K rates; (ii) determine critical fertilizer rates, critical soil test P (STP), and soil test K (STK) levels, and critical grain P and K removals for maximum productivity; and (iii) examine the response of STP and STK levels to fertilizer P and K rates. We evaluated five rates of P (0–118 kg ha −1 ) and K (0–186 kg ha −1 ) fertilizers. Since 2013, significant yield responses to P and K fertilization were frequent, except no response to K was seen at Milan during the entire study period. Application of >59 kg ha −1 P resulted in high soil P levels over time at both locations but the highest K rate (186 kg ha −1 ) brought soils from a low to only a medium level. Critical fertilizer rates and soil test levels corroborated UT's current recommendations for maximum yield.